Biomechanical and microbiological analysis of embalmed cats – acute effect of conservation - Queiroz, Andréa B. P. S. [UNESP]; Rodrigues, Alessandra [UNESP]; Cardozo, Marita V. [UNESP]; Costa, Natália T. B. [UNESP]; Soares, Laura G. [UNESP]; Fechis, Alisson D. S. [UNESP]; Oliveira, Fabrício S. [UNESP] (FapUNIFESP (SciELO), 2022)
Animals corpses in teaching and research institutions could be sources of infection for students and teachers when applied for dissection and surgical practice. This research aimed to evaluate cats’ corpses’ conservation using a new anatomic technique and vacuum package for seven days, aiming surgical practicing. A 150 mL/ kg of alcohol with 5% glycerin and 120 mL/kg of a 20% sodium chloride, 1% nitrite, and 1% sodium nitrate solution was injected on corpses sealed in vacuum packages and put on 0 to 4°C. Skin and jejunum were collected on day 0 (fresh samples/control), and traction analysis was performed for seven consecutive days. On the last day, the liquid in the plastic bags was microbiologically analyzed. There was no statistical difference between control and conservation moments (D1 and D2) in maximal rupture force of the skin, and jejunum was similar to control in D2, D4, and D6. The microbial population did not exceed 6.0x104CFU/mL in total aerobics and 4.8x104CFU/mL in total anaerobes. Biomechanics was not significantly affected, and the microbiological count was low during conservation, demonstrating the possible effectiveness of this anatomical technique for surgery training.
Keywords: Acute effect; Anatomy; Curing salt; Microorganisms; Surgery